Endoscopic Endonasal Resection of Meckel’s Cave Epidermoid Cysts: Case Discussion and Literature Review - Jehad Zakaria; Pravesh Saini; Mariya Yanovskaya; John T. Tsiang; Krishnan Ravindran; Stephen Johans; Chirag R. Patel; Anand V. Germanwala (Case Reports in Neurological Medicine)
Meckel’s cave (MC) epidermoid cysts are relatively uncommon lesions. In cases where surgical excision is indicated, resection is often carried out via a frontosphenotemporal craniotomy from an anterolateral approach or a temporal craniotomy with or without a petrosectomy for a lateral corridor; both of these routes are associated with brain retraction and potential neurovascular injury. The anterior location of MC in the middle cranial fossa makes safe access via posterior fossa-based approaches—such as the retrosigmoid approach—challenging as well. Here, we present the cases of two patients diagnosed with epidermoid cysts in MC who underwent surgical resection via an endoscopic endonasal transpterygoid approach. Near-total resection was achieved in both cases, with only mild transient neurologic disturbances postoperatively. Radiographically, no evidence of residual disease was noted in either patient. We further review the nuances of an extended endoscopic endonasal approach to these lesions.